Effect of stable stratification on dispersion within urban street canyons: A large-eddy simulation. (November 2016) - Li, Xian-Xiang; Britter, Rex; Norford, Leslie K.
Abstract: This study employs a validated large-eddy simulation (LES) code with high tempo-spatial resolution to investigate the effect of a stably stratified roughness sublayer (RSL) on scalar transport within an urban street canyon. The major effect of stable stratification on the flow and turbulence inside the street canyon is that the flow slows down in both streamwise and vertical directions, a stagnant area near the street level emerges, and the vertical transport of momentum is weakened. Consequently, the transfer of heat between the street canyon and overlying atmosphere also gets weaker. The pollutant emitted from the street level 'pools' within the lower street canyon, and more pollutant accumulates within the street canyon with increasing stability. Under stable stratification, the dominant mechanism for pollutant transport within the street canyon has changed from ejections (flow carries high-concentration pollutant upward) to unorganized motions (flow carries high-concentration pollutant downward), which is responsible for the much lower dispersion efficiency under stable stratifications. Highlights: Effects of stable stratification on street-canyon flow and pollutant are studied by LES. Stable stratifications reduce the flow and vertical transport of momentum and heat. Pollutants pool near the ground and much pollutant accumulates in street canyons. Pollutant transport mechanism under stable stratifications significantly changes.